A comparison of the effect of beaver and human‐made impoundments on stream zooplankton. Issue 5 (19th April 2018) - Czerniawski, Robert; Sługocki, Łukasz
Abstract: Small human‐made dams and beaver ponds cause significant changes in the environment of small streams. The decreased current velocity and increased water retention time in these impoundments favour the development of limnetic organisms, for example, zooplankton. However, small human‐made reservoirs are regulated, deep and narrow, whereas beavers create relatively large impoundments with numerous shallow patches and their impact on the stream zooplankton communities can be different. We compared the effect of beaver ponds and small reservoirs on the zooplankton communities in streams. Three sample collection sites were established in each stream. Site 1 was approximately 100 m upstream of the water impoundment formed by the dam. Site 2 was at the dam impoundment of the stream water. Site 3 was approximately 300 m below the dam. Beaver ponds have a larger impact on the zooplankton richness and the abundance changes compared with seminatural reservoirs not maintained by people, and a much greater impact than reservoirs regularly cleaned and regulated. Beaver ponds create heterogeneous environment that favour the occurrence of a greater number of zooplankton species compared with small reservoirs. Moreover, the increase in organic matter in the downstream areas could lead to trophic changes in the stream.